2023
DOI: 10.1111/jasp.12971
|View full text |Cite
|
Sign up to set email alerts
|

When dehumanization does (and does not) matter: Exploring the relationship between social justice motivations, avoidant behaviors, and intentions to help individuals experiencing homelessness

Abstract: Highly stigmatized groups, such as those experiencing homelessness, commonly encounter both animalistic and mechanistic dehumanization. Yet, how and when each form is related to the treatment of such groups is not well understood. We explored the relative importance of animalistic and mechanistic dehumanization in predicting behaviors to avoid and willingness to help individuals experiencing homelessness. Additionally, we probed social justice importance and engagement as potential moderators of the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…On the other hand, it is possible that prominent theological messages unintentionally reinforce an acceptance of the status quo or minimize the importance of present-day social injustices. Recent research has demonstrated that without a strong sense that social justice issues are personally important, positive attitudes toward others who are marginalized are less likely to translate into positive actions (Tausen et al, in press). In other words, if Christian institutions fail to instill a sense of personal justice importance, other fundamental messages related to common human dignity and value (e.g., the Imago Dei) and loving one’s neighbor may be less likely to be embodied.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, it is possible that prominent theological messages unintentionally reinforce an acceptance of the status quo or minimize the importance of present-day social injustices. Recent research has demonstrated that without a strong sense that social justice issues are personally important, positive attitudes toward others who are marginalized are less likely to translate into positive actions (Tausen et al, in press). In other words, if Christian institutions fail to instill a sense of personal justice importance, other fundamental messages related to common human dignity and value (e.g., the Imago Dei) and loving one’s neighbor may be less likely to be embodied.…”
Section: Discussionmentioning
confidence: 99%
“…Two additional items probed social justice attitudes and actions separate from faith (see Tausen et al, in press). Responses were assessed using a 100-point analogue scale with appropriate anchors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Bastian & Haslam, 2011). The measure has been commonly adapted to measure dehumanization perceptions of individuals experiencing homelessness (e.g., Tausen et al, 2023).…”
Section: Methodsmentioning
confidence: 99%